Improvement in the high temperature mechanical properties of additively manufactured Ti–48Al–2Cr–2Nb alloy using heat treatment. (February 2023) - Youn, Seong-June; Kim, Young-Kyun; Kim, Hyoung Seop; Lee, Kee-Ahn
Abstract: Gamma Ti–48Al–2Cr–2Nb (Ti4822) alloy, which is manufactured by an electron beam melting (EBM) process, has excellent ductility but poor high-temperature strength, because it has a near gamma structure. The objective of this study was to control the microstructure of Ti4822 by considering various forms of heat treatment to improve the mechanical properties at room and high temperatures. The heat treatment conditions were varied to create nearly lamellar (NL) and fully-lamellar (FL) structures. First, the EBM-built NL-Ti4822 exhibited a lamellar structure with an average layer thickness of about 92 nm and equiaxed γ-phase particles with a size of several tens of micrometers. On the other hand, the EBM-built FL-Ti4822 had an average lamellar thickness of about 347.2 nm, but in this case the equiaxed γ phase was not observed. The results of the room- and high-temperature compression test showed that the mechanical properties of the two heat-treated materials were significantly superior to those of the as-built Ti4822 across all temperature ranges. Moreover, both materials were highly ductile at room and high temperature despite having a lamellar structure, and exhibited intensified yield stress anomaly and dynamic recrystallization as the fraction of lamellar structure increased. Based on the above results obtained by subjecting the materials to different heat treatment methods, the effects of the microstructures of the two materials on the mechanical properties and deformation mechanisms at room and high temperatures were investigated. Graphical abstract: Image 1 Highlights: The microstructure of EBM-built Ti4822 was controlled to nearly lamellar and fully lamellar structures by heat treatment. Mechanical properties were significantly improved in all temperature ranges after heat treatment. Heat-treated Ti4822 have several times superior room temperature ductility than conventionally processed Ti4822.